Conventional fluorscopy-guided vs zero-fluorscopy catheter ablation of supraventricular tachycardias. (19th May 2022) - Prolic Kalinsek, T; Sorli, J; Jan, M; Sinkovec, M; Antolic, B; Klemen, L; Zizek, D; Pernat, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Traditionally, X-ray fluoroscopy is used during catheter ablation procedures. The utilisation of ionising radiation carries non-negligible stochastic and deterministic risks to the health of both the patient and the professional staff. These effects are cumulative and behave in a linear no-threshold manner and, as such, are especially important in paediatric populations (1). The importance of reducing ionising radiation exposure has been recognised by the American College of Cardiology, which recommends the ALARA (as low as reasonably achievable) principle in all interventional laboratories (2). In recent years, advances in three-dimensional electroanatomical mapping systems and their utilisation have enabled the near-zero and zero-fluoroscopy approaches to be studied (3). Purpose: The aim of this study was to evaluate the safety and efficacy of zero-fluoroscopy catheter ablation for supraventricular tachycardias (SVT). Methods: 584 consecutive patients referred to our institution for catheter ablation of SVT were analysed. Patients were categorised into two groups; zero-fluoroscopy (ZF) group and conventional fluoroscopy (CF) group. Patient characteristics, procedural information, and follow-up data were compared. Results: The ZF group had a higher proportion of paediatric patients (42.2% vs 0.0 %; p < 0.001), resulting in a younger age (30.9 ± 20.3 years vs 52.7 ± 16.5 years; p < 0.001) and lower BMI (22.8 ± 5.7 kg/m2 vs 27.0 ± 5.4 kg/m2; p < 0.001). Procedure time was shorter in the ZF group (94.2 ± 50.4 min vs 104.0 ± 54.0 min; p = 0.002). There were no major complications and the rate of minor complications did not differ between groups (0.0% vs 0.4%; p = 0.304). Acute procedural success as well as the long-term success rate when only the index procedure was considered did not differ between groups (92.5% vs 95.4%; p = 0.155; 87.1% vs 89.2%; p = 0.422). When repeated procedures were included, the long-term success rate was higher in the ZF group (98.3% vs 93.5%; p = 0.004). The difference can be partially explained by the operators' preferences. Conclusion: The safety and efficacy of ZF procedures in adult and paediatric populations are comparable to that of CF procedures.